2017
DOI: 10.3390/microorganisms5040067
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Step Bioconversion Process for Canolol Production from Rapeseed Meal Combining an Aspergillus niger Feruloyl Esterase and the Fungus Neolentinus lepideus

Abstract: Rapeseed meal is a cheap and abundant raw material, particularly rich in phenolic compounds of biotechnological interest. In this study, we developed a two-step bioconversion process of naturally occurring sinapic acid (4-hydroxy-3,5-dimethoxycinnamic acid) from rapeseed meal into canolol by combining the complementary potentialities of two filamentous fungi, the micromycete Aspergillus niger and the basidiomycete Neolentinus lepideus. Canolol could display numerous industrial applications because of its high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 47 publications
2
39
0
Order By: Relevance
“…Esterase activity was assayed spectrophotometrically at either 37°C and 55°C for AnFaeA or 37°C and 50°C for AnFaeB and ChlE, as previously described (Odinot et al, 2017), by monitoring the A335 with respect to the rate of hydrolysis of 0.032 mM of the enzyme substrate in 88 mM of a 3-(N-morpholino)propanesulfonic acid (MOPS) buffer (pH 5.5 for AnFaeA and pH6 for AnFaeB and ChlE). The synthetic substrates used were methyl sinapate for AnFaeA, methyl caffeate and methyl p-coumarate for AnFaeB, and chlorogenic acid for ChlE.…”
Section: Enzyme Activity Assaymentioning
confidence: 99%
See 3 more Smart Citations
“…Esterase activity was assayed spectrophotometrically at either 37°C and 55°C for AnFaeA or 37°C and 50°C for AnFaeB and ChlE, as previously described (Odinot et al, 2017), by monitoring the A335 with respect to the rate of hydrolysis of 0.032 mM of the enzyme substrate in 88 mM of a 3-(N-morpholino)propanesulfonic acid (MOPS) buffer (pH 5.5 for AnFaeA and pH6 for AnFaeB and ChlE). The synthetic substrates used were methyl sinapate for AnFaeA, methyl caffeate and methyl p-coumarate for AnFaeB, and chlorogenic acid for ChlE.…”
Section: Enzyme Activity Assaymentioning
confidence: 99%
“…In this context, SFM and RSM, which are cheap, abundant, and rich in phenolics, make perfectly suitable candidates. It is worth noting that only few studies have reported the use of these two raw materials for the production of phenolic acids and derivatives like vinyl phenols (Kreps et al, 2014;Odinot et al, 2017).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This is based on a previous report that sinapine esterase catalyzed the hydrolysis of sinapine to sinapic acid (Nurmann & Strack, ). In addition, a recent study compared the impacts of three different recombinant strains from Aspergillus niger on enzymatic hydrolysis of sinapine, and found that the feruloyl esterases from A. niger (BRFM451) showed highest hydrolysis sinapic acid yields of 68% to 76% (Odinot et al, ). Therefore, for continuous generation of sinapic acid, sinapine esterase or feruloyl esterase could be a more effective alternative than alkaline hydrolysis of canola meal.…”
Section: Discussionmentioning
confidence: 99%